Biodiesel etílico filtrado de óleo residual de soja: desempenho de um trator agrícola na operação de gradagem - Checchio Grotta, Danilo Cesar [UNESP]; Lopes, Afonso [UNESP]; Angeli Furlani, Carlos Eduardo [UNESP]; Da Silva, Rouverson Pereira [UNESP]; Dos Reis, Gustavo Naves [UNESP]; Cortez, Jorge Wilson [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
Filtered ethyl ester biodiesel from residual soybean oil: performance of an agricultural tractor in the disk harrow operation. This test was conducted to evaluate the performance of an agricultural tractor using a mixture of biodiesel and petroleum diesel. The experiment was conducted at FCAV-Unesp, Jaboticabal, using a 4x2 AFWD tractor with 73.6 kW (100 hp @ 2,300 rpm) of power in the motor, pulling a disk harrow. The biodiesel used was of the ethyl type, filtered, and produced from residual soybean oil. The experimental design was completed randomized in factorial scheme (4x5), with 20 treatments and 4 repetitions, in which 5 ratios of biodiesel and petroleum diesel mixtures were combined (0 and 100%, 25 and 75%, 50 and 50%, 75 and 25% and 100 and 0%), with 4 displacement runs. The analyzed variables were traction bar power, engine rotation and displacement speed. The results evidenced that the mixture ratio (biodiesel and petroleum diesel) did not compromise tractor performance until the limit of 50%.
Filtered ethyl ester biodiesel from residual soybean oil: performance of an agricultural tractor in the disk harrow operation
Keywords: Biodiesel; tractor performance; disk harrow